The Loss of the Right of Non-Muslim Substitute Heirs to Inherit (A Study of the Wates Religious Court Decision Number 84/Pdt.G/2022/Pa.Wt) - Ghina Marta Salmaa Salsabila; Riyanta Riyanta (CV. Publikasi Indonesia, 2026)
The Wates Religious Court's decision in case number 84/Pdt.G/2022/PA.WT ruled not to appoint a non-Muslim substitute heir from the first wife's lineage due to their Christian faith, as per Islamic inheritance law, which prohibits non-Muslims from inheriting. This study examines the judge's reasoning and considers the values of justice, legal certainty, and legal utility. Using an empirical juridical approach supported by library and field research, the study finds that the judge's decision aligns with the Compilation of Islamic Law (KHI), particularly Article 171 letter (c), which prohibits non-Muslims from inheriting. However, the judge could have utilized the Supreme Court Jurisprudence No. 1/Yur/Ag/2018 to allow for a mandatory will and made a legal discovery by interpreting the Civil Code more extensively. While the decision adheres to legal certainty under Islamic law, it does not align with the principles of justice or legal utility, nor does it reflect the legal certainty found in the Civil Code and Supreme Court jurisprudence.